The patterns and determinants of price setting in the Belgian industry - David Cornille; Maarten Dossche (European Central Bank (ECB), 2006)
This paper documents the patterns and determinants of price setting in the Belgian industry. We analyse the micro data underlying the Producer Price Index (PPI) over the period from February 2001 to January 2005. On average only one out of four prices changes in a typical month, whereas the absolute size of a price change amounts to 6%. The frequencies of price adjustment are particularly heterogeneous across sectors, which is determined by heterogeneity in the market and cost structure. We find no signs of downward nominal rigidity. A joint analysis of sizes and frequencies of price adjustment across time shows that price setting is characterised by both time- and state-dependent pricing. About 38% of the exported goods are aected by pricing-to-market.
Keywords: D40; E31; 330; nominal price rigidity; pricing-to-market; producer price setting; staggering; state-dependent pricing; time-dependent pricing; Preismanagement; Preisrigidität; Belgien